THU0235 Ankylosing spondylitis and rheumatoid arthritis hospitalisation trends in the us: data from national inpatient sample. (12th June 2018) - Karmacharya, P.; Shrestha, P.; Dhital, R.; Poudel, D.R.
Abstract : Background: Ankylosing spondylitis (AS) imposes significant morbidity and disability in the affected population. Hospitalisation trends provide an insight as to burden of disease and long-term data is lacking. We evaluated AS related hospitalisation trends in the US from 2001–13, comparing it to the more common inflammatory arthritis- rheumatoid arthritis (RA). Objectives: To evaluate AS related hospitalisation trends in the US in comparision to the more common inflammatory arthritis- RA Methods: Using the Nationwide Inpatient Sample (NIS) data from 2009–2011, we identified patients≥18 years with AS and RA at primary diagnosis positions based on ICD-9 codes 720.0 and 714.0, 714.2, 714.30–714.33 respectively. We also excluded patients with psoriatic arthritis and inflammatory bowel disease to improve the specificity of codes used. We used the trend weight (contained in the variable TRENDWT) supplied by HCUP to study the annual trends of hospitalizations in AS and RA (2001–13). We used Stata version 13.0 (College Station, TX) and Joinpoint regression analysis software to calculate yearly trends. Results: NIS database from 2001–2013 contained 36 883 (weighted count, n=175, 356) patients with RA and 1377 (weighted count- 6, 554) patients with AS. A decreasing trend in AS and RA hospitalizations was noted with an annual percentage change (APC) of 5.35 and 4.28 respectively (p<0.05) (table 1 and figure 1). Conclusions: While recent studies have shown a rise in incidence of AS, the hospitalisation rates have declined similar to RA. Our study findings may reflect increased recognition of inflammatory back pain in the primary care setting and prompt referral and diagnosis due to improved imaging techniques of the spine and pelvis. Furthermore, the use of biologics, such as TNF and IL-6 inhibitors have significantly improved outcomes. Disclosure of Interest: None declared